Correction of age-associated deficiency in germinal center response by immunization with immune complexes - Zheng, Biao (Clinical immunology (Orlando, Fla.), 2007)
In aging, both primary and secondary antibody responses are impaired. One of the most notable changes in age-associated immune deficiency is the diminished germinal center (GC) reaction. This impaired GC response reduces antibody affinity maturation, decreases memory B cell development, and prevents the establishment of long-term antibody-forming cells in the bone marrow. It is of great importance to explore novel strategy in improving GC response in the elderly. In this study, the efficacy of immunization with immune complexes in overcoming age-associated deficiency in GC response was investigated. We show that the depressed GC response in aged mice can be significantly elevated by immunization with immune complexes. Importantly, there is a significant improvement of B cell memory response and long-lived plasma cells. Our results demonstrate that immune complex immunization may represent a novel strategy to elicit functional GC response in aging, and possibly, to overcome age-related immune deficiency in general